Penggunaan Bahasa Gaul di Media Sosial TikTok dan Dampaknya pada Komunikasi Antargenerasi - Nur Fatimah; Ramly Ramly; Sakinah Fitri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This research discusses the use of slang on TikTok social media and its impact on intergenerational communication, especially Generation Y and Generation Z. This research is motivated by the rise of new terms on TikTok that are not only used in an online context, but also carried over into everyday conversations. The main purpose of this study is to describe the forms of slang use on TikTok and describe its impact on cross-generational communication. This study uses a qualitative approach with a descriptive method. Data was obtained through documentation of TikTok video uploads containing slang and the distribution of questionnaires to respondents from Generations Y and Z. The results of the study showed that slang on TikTok was dominated by lexical forms in the form of abbreviations, puns, and the absorption of foreign languages used in informal contexts. The use of this language has a two-way impact, namely strengthening relationships through a relaxed and actual communication style, but at the same time causing a gap in understanding for users who are unfamiliar with certain terms, thus potentially triggering communication barriers. These findings are in line with Labov's theory of language variation which asserts that differences in age and social context influence language choice. Overall, the study concluded that TikTok slang not only serves as a means of expression, but also shapes the dynamics of intergenerational communication in a digital society.